Packed‐Bed Microreactor Under Taylor Flow for MOFs Catalyst Testing Demonstrated on Phenylacetylene Hydrogenation - Anchu Ashok (14152020) (2024)
Metal‐Organic Frameworks (MOFs) represent a highly promising class of materials with diverse applications, particularly as catalytic materials. However, their synthesis typically yields powders available only at laboratory‐scale quantities, usually in the gram range or less. This study addresses the challenge of testing limited amounts of MOF catalysts for demanding applications, such as multiphase gas‐liquid‐solid reactions in flow, utilizing a packed‐bed microreactor. Specifically, we investigate the performance of a nanoparticle (NP) ‐immobilized Pd@UiO‐66 MOF catalyst in the selective semi‐hydrogenation of phenylacetylene to styrene, serving as a model reaction. Maintaining the Taylor flow regime upstream of the catalyst bed was crucial to ensure reproducible and reliable experimental results. We conducted 88 experiments at varying liquid flow rates, temperatures ranging from 15 to 45 °C, and relative pressures spanning 0.28 to 8 bar. Styrene selectivity within the range of 80–92.3 % was achieved at phenylacetylene conversions below 20 %. Notably, the optimal condition for styrene selectivity (70 %) was attained at 98.9 % phenylacetylene conversion under the lowest H2 pressure and highest temperature, demonstrating the significance of low H2 concentration for achieving optimal styrene selectivity. Remarkably, the catalyst exhibited stable activity and selectivity over a 20 h testing period, indicating its robust performance under prolonged reaction conditions. This study demonstrates the potential of the proposed catalyst testing system as a rapid and efficient approach for early‐stage exploration studies, particularly when limited quantities of catalyst, typically in the gram scale or less, are available. Other Information Published in: ChemistrySelect License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/slct.202400978